Evaluation of performance of sorghum varieties grown in Tokyo for sugar accumulation and its correlation with vacuolar invertase genes SbInv1 and SbInv2. (2nd October 2018) - Morey, Shamitha Rao; Hashida, Yoichi; Ohsugi, Ryu; Yamagishi, Junko; Aoki, Naohiro
ABSTRACT: The sugar-accumulating potential of global and local sweet and grain sorghum varieties were tested under the local conditions. The basis for this study was the dependency of sugar accumulation on temperature and photoperiod. Thus, the efficacy of cultivars as a bioenergy source would need to be determined based on their performance under the local environmental conditions. A strong correlation of sucrose content with brix was observed, enabling large-scale screening of varieties for high sucrose content. The morphological characteristics inherent in sweet sorghum, such as tall stems, greater number of leaves and a longer vegetative period, were found to correlate with the total stem sugar content. Assessment of sugars along the stem revealed maximum sugar accumulation in the upper intermediate to upper internodes in most of the varieties tested. The maximum theoretical ethanol yield (MTEY), a function of brix and juice yield, was determined as a better indicator of testing the performance of a variety as a potential source of bioethanol, mainly due to a negative correlation of stem juiciness and sucrose content in the varieties tested. Further, the relative expression of vacuolar invertase genes, SbINV1 and SbINV2, was studied, and a strong negative correlation of SbINV2 to stem sucrose content was observed. This reveals a possibility of involvement of vacuolar invertase gene, SbINV2, in sugar accumulation in sweet sorghum stems, and as a key candidate for molecular breeding studies for higher stem sugar content.